2013
DOI: 10.4238/2013.september.13.3
|View full text |Cite
|
Sign up to set email alerts
|

Methylation regulation of liver-specific microRNA-122 expression and its effects on the proliferation and apoptosis of hepatocellular carcinoma cells

Abstract: ABSTRACT. The regulation mechanism and significance of microRNA-122 (miRNA-122) expression are unclear. The aim of this study was to investigate the effects of DNA methylation on liverspecific miRNA-122 expression, cell proliferation, and apoptosis in hepatocellular carcinoma. Methylation of the miRNA-122 promoter region was detected through methylation sequencing. The level of miRNA-122 expression was measured using real-time quantitative polymerase chain reaction. The proliferation and apoptosis of hepatocel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…It is not possible to conclusively rule out an association between shift work and liver unhealthiness by our observations of relative young and healthy workers, since adverse effects of circadian disruption on liver health have been found in both animal (Filipski et al, 2009;Konturek et al, 2011) and human studies (Copertaro et al, 2008;Larsson et al, 2009;Ma et al, 2009;Nakamura et al, 1998) and have been supported by studies on gene expression (Szantoova et al, 2011). Determining the exact effects of RSW on liver health in the future may require longer monitoring and other surrogate markers, such as microRNA-122 (Arataki et al, 2013;Spaniel et al, 2013;Waidmann et al, 2012;Xing et al, 2013), aspartate aminotransferase, glutamyl transpeptidase, and bilirubin levels (Bulum et al, 2011). Besides conventional parameters, one can measure the body temperature and monitor the melatonin rhythm, to demonstrate the mismatch between central and peripheral rhythm among shift workers (Cermakian & Boivin, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible to conclusively rule out an association between shift work and liver unhealthiness by our observations of relative young and healthy workers, since adverse effects of circadian disruption on liver health have been found in both animal (Filipski et al, 2009;Konturek et al, 2011) and human studies (Copertaro et al, 2008;Larsson et al, 2009;Ma et al, 2009;Nakamura et al, 1998) and have been supported by studies on gene expression (Szantoova et al, 2011). Determining the exact effects of RSW on liver health in the future may require longer monitoring and other surrogate markers, such as microRNA-122 (Arataki et al, 2013;Spaniel et al, 2013;Waidmann et al, 2012;Xing et al, 2013), aspartate aminotransferase, glutamyl transpeptidase, and bilirubin levels (Bulum et al, 2011). Besides conventional parameters, one can measure the body temperature and monitor the melatonin rhythm, to demonstrate the mismatch between central and peripheral rhythm among shift workers (Cermakian & Boivin, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Its antitumor activity in solid tumors including HCC has been elucidated in previous studies [ 53 ]. Xing et al [ 54 ] have demonstrated that decitabine could facilitate the expression of miR-122 via inhibition of methylation in HCC cells. More importantly, Skårn et al [ 55 ] have demonstrated that miR-142 is epigenetically restrained by DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Serum AFP is often elevated in HCC patients, but HCC patients could have normal or low level of AFP, patients with CH and CR could have elevated serum AFP, as shown in our data. Although there are studies in protein or RNA expressions, epigenetics and microRNAs in HCC 15 , fundamentally intensive genomic abnormalities are characteristics of all cancers including HCC, especially at advanced stages. The method we proposed here could identify over two thirds of HCC no more than 50 mm, more than half of HCC no more than 30 mm, with no positive results from 8 CH and CR patients in our study.…”
Section: Discussionmentioning
confidence: 99%